The great Gatsby [videorecording (DVD)] - Luhrmann, Baz; Luhrmann, Baz; Luhrmann, Baz; Pearce, Craig; DiCaprio, Leonardo; Maguire, Tobey, 1975-; Mulligan, Carey, 1985-; Edgerton, Joel, 1974-; Fisher, Isla, 1976-; Clarke, Jason, 1969-; Armstrong, Craig, 1959-; Fitzgerald, F. Scott (Francis Scott), 1896-1940 (Distributed by Warner Home Video, 2013)
The Great Gatsby follows viable writer Nick Carraway as he leaves the Midwest and comes to New York City in the spring of 1922. Chasing his own American dream, Nick lands next door to Jay Gatsby, and across the bay from his cousin, Daisy, and her husband, Tom Buchanan. Nick is drawn into the captivating world of the rich and their loves and deceits. As he bears witness, he pens a tale of impossible love, incorruptible dreams, and tragedy, and holds a mirror to our own modern times and struggles.